THE EFFECTS OF LISTENING TO PREFERRED MUSIC ON POSITIVE EMOTIONS AND SELF-REGULATORY STRENGTH DEPLETION PATTERNS USING ISOMETRIC HANDGRIP EXERCISE. - BITTNER, PATRICIA JENNIFER (My University, 2009)
Self-regulation refers to the ability to override one behaviour, thought, or emotion
and replace it with another (Baumeister & Heatherton, 1996). Baumeister et ai. (1998)
propose that self-regulation is governed by a form of strength that varies from person to person and can be depleted by engaging in tasks that require self-regulation. Although self-regulation strength can be depleted, it may also be replenished through rest and other hypothesized mechanisms. Positive emotion has been suggested as a way to replenish depleted self-regulatory reserves (Tice et aI., 2007). The purpose of the CUlTent study was to investigate the effects of listening to self-selected uplifting music on positive emotional states and the effect of varying positive emotional states on self-regulatory strength depletion patterns. It was hypothesized that the group that listened to a selection of prefened music would show an increase in positive emotion on the PANAS measure and that the positive emotion induction would serve as a replenishment of self-regulation, which would lead to amelioration of depletion effects on a handgrip squeezing exercise performed after this induction. The study employed a between subjects, repeated measures design. Participants were 90 sedentary university students (Mage =22.90 ± 7.18) who were randomly assigned to one of three conditions; (Stroop) Depletion/Music (emotion induction), Depletion/No Music (quiet rest control), or No Depletion/No Music (no depletion control and quiet rest control). After controlling for initial positive emotion scores, ANOVA results revealed that participants showed significantly higher scores on the positive emotion scale of the PANAS, F(2,87) = 7.84, p < .01. 112 =.73 after listening to music than engaging in quiet rest. The results further illustrate that the change from pre- to post- manipulation in raw mean scores for each condition did not differ significantly in the length of time that participants held onto the handgrip during the endurance trial at 50% MVC, F(2,87) = 0.30, p =.74, ,,2 = .01. After 18 participants were eliminated due to questionably low (:=:; 5) RPE ratings on the pre-test, the ANOVA was completed again, and no significant differences emerged, F(2,68) = .68, p = .51, ,,2 = .02. Although the results do not demonstrate that positive emotion has an impact on selfregulatory
strength depletion patterns, the current findings are discussed with respect to previous research done by Tice et al. (2007) and in light of Fredrickson's broaden and build theory and limitations. Further research is warranted to gain a better understanding
of the relationship between music, positive emotion and self-regulation for exercise.
Keywords: Kinesiology; Kinesiology